Dopamind+: Mobile-Based Application to Prevent and Treat Mental Health Disorders in Adolescents - Rahmadiannisa, Mutiara S.; Firdaus, Fadli S.; Manaf, Irfan M.; Putra, Kadek W.P. (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
To achieve the third goal of the SDGs, which is to ensure a healthy life and promote well-being for individuals of all ages, mental health in Indonesia has been insufficiently addressed. Mental health disorders prevalent in the community include stress, depression, and even suicide. Factors triggering conditions, such as irregular sleep, especially among women, can affect the regularity of their menstrual cycles. Therefore, preventive measures are needed by creating the Dopamind+ application. The purpose of developing this application is to 1) Analyze the impact of the Dopamind+ application on users who are likely to experience mental health disorders, 2) Reduce the incidence of mental health disorders, 3) Support innovation in mental health issues by collaborating with technology, and 4) Create a mobile-based application that provides healthcare services and education, especially for teenagers. Hopefully, this application will help users access information, support, and mental health services. In addition, it can demonstrate the importance of cross-sector collaboration in providing holistic and integrated mental health services and has the potential to improve users' quality of life by reducing levels of stress, depression, and risk of suicide; in making this application, we used the design thinking method. This approach is used to understand user needs and design solutions better accordingly. The Empathize stages help in understanding the experiences and challenges faced by individuals regarding mental health. Define and identify the problems you want to solve and direct innovation. Ideate makes it possible to generate a variety of creative solution ideas. Prototype allows developers to test those ideas, and testing helps evaluate application performance and receive user feedback. The findings highlighted in this application are SOS, which will enable users to trigger emergency signals, and beacon signals, which will enable them to ask for help from those around them in mental health emergencies. The target users of the Dopamind+ application are classified based on age, gender, and diseases/genetics. Stakeholders in this application include health departments, social services, users, police, fire departments, developers, researchers, academicians, and relevant organizations. The limitations of the Dopamind+ application are that it uses the English language, requires a user email password, and employs features designed for all groups, especially teenagers prone to mental health issues. This application is accessible via mobile platforms such as Android and iOS. The features include Smart to-do list, Red Day tracker, Educare and Counseling, Virtual Community, Sleep tracker, SOS, and Stress tracker.